A Decade of Internationalization of the Brazilian Symposium on Software Engineering: The Good, the Bad, and the Ugly - Mendonça, Nabor; Teixeira, Leopoldo; Soares, Sergio; Garcia, Vinicius Cardoso; Kulesza, Uirá; França, César; Lucrédio, Daniel; Cirilo, Elder; Machado, Ivan (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Increasing the international visibility of their papers is an old desire of the Brazilian Symposium on Software Engineering (SBES) community. In that regard, the community has taken several actions throughout the years, such as incentivizing the submission of papers in English and, since 2009, publishing the symposium’s proceedings in closed-access international digital libraries. However, thus far, there have been no studies aimed at evaluating the real impact of such initiatives. In this paper, we report on a bibliometric study whose goal was to assess the impact of SBES’s internationalization effort. To this end, we have collected and classified language and citation data from papers published in the SBES Research Track from 2010 to 2020. One can examine the results of our study from multiple views. A more generous view (the “good”) reveals that, by obtaining around 40-60% of its citations from the international community, SBES might have achieved its internationalization goals with reasonable success. A more rigorous view (the “bad”), in turn, highlights that, by still attracting at least 40% of its citations from the Brazilian community, SBES’s internationalization might not compensate for its inevitable weight on the community, i.e., the international libraries’ publication costs and their non-compliance to well established Open Science principles. Finally, a more critical view (the “ugly”) calls attention to the relatively high percentage (25-50%) of SBES papers’ self-citations, well above the average rate in Computer Science and other disciplines.